2016
DOI: 10.1108/ijcst-12-2015-0134
|View full text |Cite
|
Sign up to set email alerts
|

Fabric defect detection via learned dictionary-based visual saliency

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Dictionary learning-based approaches have shown good results for fabric defect detection [3]. Li et al [32] proposed a learned dictionary-based visual saliency approach for FDD. is approach partitioned the image into blocks, and a dictionary is then constructed for both normal and defective image samples based on sorted local binary features correlation.…”
Section: Dictionary Learning-based Approachesmentioning
confidence: 99%
“…Dictionary learning-based approaches have shown good results for fabric defect detection [3]. Li et al [32] proposed a learned dictionary-based visual saliency approach for FDD. is approach partitioned the image into blocks, and a dictionary is then constructed for both normal and defective image samples based on sorted local binary features correlation.…”
Section: Dictionary Learning-based Approachesmentioning
confidence: 99%
“…Liu et al developed a context-based local texture saliency detection model, which shows promising performance for fabric defect detection [20]. Li et al employed a learned dictionary to generate saliency maps for fabric defect images, and then an improved valley-emphasis method is applied to segment the defect region based on the saliency maps [21]. Guan et al proposed the integrated model of top-down and bottom-up visual attention, and the adapted threshold method is employed to detect the defect region [22].…”
Section: A Saliency Detectionmentioning
confidence: 99%
“…The traditional methods can be divided into four categories: statistical, spectral, model-based and dictionary learning method. The statistical method splits the test image into image block with the same size and extracts their statistical texture feature such as histogram (Li et al , 2019a), gray-level co-occurrence (Dash, 2018) and LBP (Li et al , 2016), and then the defective image block is identified by calculating the feature difference between the test image block with the other blocks. Therefore, the performance of these methods depends on the suitable image block size, and they cannot effectively detect the defects with small size.…”
Section: Related Workmentioning
confidence: 99%